2003
DOI: 10.1183/09031936.03.00115402
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension in chronic obstructive pulmonary disease

Abstract: Pulmonary hypertension in chronic obstructive pulmonary disease. J.A. Barberà, V.I. Peinado, S. Santos. #ERS Journals Ltd 2003. ABSTRACT: Pulmonary hypertension is a common complication of chronic obstructive pulmonary disease (COPD). Its presence is associated with shorter survival and worse clinical evolution. In COPD, pulmonary hypertension tends to be of moderate severity and progresses slowly. However, transitory increases of pulmonary artery pressure may occur during exacerbations, exercise and sleep. Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
306
2
25

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 389 publications
(348 citation statements)
references
References 123 publications
(190 reference statements)
15
306
2
25
Order By: Relevance
“…We observed that one quarter of our COPD patients displayed pulmonary endothelial dysfunction, which is in agreement with our subsequent results observed in a larger series [8]. No data are available in the literature for further comparison, but a ~30% incidence of pulmonary hypertension in COPD patients has been reported [10]. In the study of Peinado and colleagues in mild COPD patients (mean ± SD: 24.9 ± 22.9 %), the dilator response to acetylcholine was diminished as compared to non smokers (40.1 ± 22.0 %), without reaching statistical significance.…”
Section: Endothelial Dysfunctionsupporting
confidence: 92%
See 1 more Smart Citation
“…We observed that one quarter of our COPD patients displayed pulmonary endothelial dysfunction, which is in agreement with our subsequent results observed in a larger series [8]. No data are available in the literature for further comparison, but a ~30% incidence of pulmonary hypertension in COPD patients has been reported [10]. In the study of Peinado and colleagues in mild COPD patients (mean ± SD: 24.9 ± 22.9 %), the dilator response to acetylcholine was diminished as compared to non smokers (40.1 ± 22.0 %), without reaching statistical significance.…”
Section: Endothelial Dysfunctionsupporting
confidence: 92%
“…We suggest that in former smokers, endothelial dysfunction of pulmonary arteries is associated with impairment of both spontaneous resting tone and cGMP-mediated dilation of airways, establishing a biological link between pulmonary arterial and bronchial functions. To our best knowledge, comparison of arterial and bronchial pharmacological functions obtained from the same lung sample has never been made, and the description of dysfunction of pulmonary arteries has been assessed in a very limited number of studies [4,10,11]. A recent pulmonary perspective supported by the National Heart, Lung, and Blood Institute stated that there is a need for methods linking in vitro observations to in vivo disease state with regard to airway smooth muscle function [12].…”
Section: Introductionmentioning
confidence: 99%
“…An important cause of V' A /Q' inequality might be the change of pulmonary blood flow distribution due to a vasoconstrictive reaction that includes HPV, endothelial dysfunction and inflammation. 5,9 The obviously increased PVRI and the during rest, exercise and exacerbation in patients with severe COPD.…”
Section: Discussionmentioning
confidence: 99%
“…9 Among all of the possible mechanisms, hypoxic pulmonary vasoconstriction (HPV) might play an important role in inducing PH during exercise, because exercise-induced PH was improved by supplemental oxygen. The significant decrease of PvO 2 during exercise might enhance HPV resulting in significant PH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation